Society and Religious Moderation: Strategies of Community and Religious Leaders in Enhancing Adolescents' Religious Motivation - Chairul Tamimi; Emzinetri Emzinetri; Dilla Astarini (Jurnal Indonesia Studi Moderasi Beragama, 2025)
Background: Rapid social and technological changes have made it difficult for adolescents to maintain strong religious values, highlighting the need for community and religious leaders to guide and support them. Objective: This study aims to examine the efforts of community and religious leaders in enhancing the religious motivation of adolescents in Karang Agung Village, Tanjung Sakti District, Lahat Regency, South Sumatra. Method: This research employs a field research approach and was conducted in 2023. The study involved 15 participants selected through purposive sampling. Data were collected from primary and secondary sources using interviews, documentation, and observation methods. Data validity was ensured through triangulation, and data analysis followed Miles & Huberman’s interactive analysis model. Results: Community and religious leaders play a key role in fostering adolescents' religious awareness and behavior by serving as role models and providing positive guidance, facilities, and activities. Conclusion: The active role of community and religious leaders is crucial in shaping adolescents' religious motivation by offering guidance, support, and positive engagement. Contribution: This study contributes to understanding the significance of leadership in promoting religious values among youth and provides insights for policymakers and educators in designing community-based religious programs.